2019 IEEE Information Theory Workshop (ITW) 2019
DOI: 10.1109/itw44776.2019.8989384
|View full text |Cite
|
Sign up to set email alerts
|

LDPC Code Design for Delayed Bit-Interleaved Coded Modulation

Abstract: This paper investigates the design and performance of delayed bit-interleaved coded modulation (DBICM) with lowdensity parity-check (LDPC) codes. For Gray labeled squareary quadrature amplitude modulation (QAM) constellations, we investigate the optimal delay scheme with the largest spectrum efficiency of DBICM for a fixed maximum number of delayed time slots and a given signal-to-noise ratio. When analyzing the capacity of DBICM, we find two important properties: the capacity improvement due to delayed coded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Numerical results showed that a 0.5 dB gain was achieved by the optimal labeling scheme designed with their criteria compared to BICM-ID in 16-QAM. A low density parity check (LDPC) code design for DBICM based on the paragraph extrinsic information transfer (EXIT) was proposed in [ 23 ]. They achieved a signal-to-noise ratio gain of 0.5 dB to 0.1 dB over the BICM counterparts at a code rate ranging from 0.25 to 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical results showed that a 0.5 dB gain was achieved by the optimal labeling scheme designed with their criteria compared to BICM-ID in 16-QAM. A low density parity check (LDPC) code design for DBICM based on the paragraph extrinsic information transfer (EXIT) was proposed in [ 23 ]. They achieved a signal-to-noise ratio gain of 0.5 dB to 0.1 dB over the BICM counterparts at a code rate ranging from 0.25 to 0.5.…”
Section: Introductionmentioning
confidence: 99%